REFLECTIVE JOURNALS VIA PADLET: ENHANCING EFL STUDENTS’ RECOUNT TEXTS COMPOSITION - Khanifa Ziazdatul Khoir; Arik Susanti (Wiralodra English Journal, 2025)
This study aimed to evaluate the effectiveness of employing reflective journaling via Padlet to compose recount texts. A quasi-experimental design was used with an experimental and a control group. The study included 62 junior high school students as the sample of this study, with 32 students in the experimental group and 30 in the control group. Data were gathered by administering a writing test, which included both a pretest and a posttest that consisted of recount texts essay instructions. The acquired data were evaluated using statistical methods, notably the independent sample t-test. The results showed significant differences between the experimental and control groups. The significance result (2-tailed) of .000, which was smaller than the alpha value of 0.05, clearly indicated this. To sum up, using reflective journals via Padlet demonstrated to be an effective strategy for enhancing students’ recount text writing skills, particularly in structuring ideas coherently and improving grammatical accuracy. Furthermore, it is recommended that teachers incorporate reflective journals into their classes to encourage self-reflection and continuous improvement.